PROJECT APPROACH TO THE ORGANIZATION OF STUDENTS' INDEPENDENT LEARNING IN THE CREDIT-MODULAR SYSTEM (TAMADDUN NURI JURNALI, 2025)
The article examines the main aspects of the project method, including its definition and essential features, and the specific features of its use in educational practice. This article provides a clear idea of what the project method is, what advantages it can have, and how it can be applied in higher education.